The Role of Lactate-Mediated Metabolic Coupling between Astrocytes and Neurons in Long-Term Memory Formation - Steinman, Michael Q.; Gao, Virginia; Alberini, Cristina M. (Frontiers in Integrative Neuroscience, 2016)
Long-term memory formation, the ability to retain information over time about an experience, is a complex function that affects multiple behaviors, and is an integral part of an individual’s identity. In the last 50 years many scientists have focused their work on understanding the biological mechanisms underlying memory formation and processing. Molecular studies over the last three decades have mostly investigated, or given attention to, neuronal mechanisms. However, the brain is composed of different cell types that, by concerted actions, cooperate to mediate brain functions. Here we consider some new insights that emerged from recent studies implicating astrocytic glycogen and glucose metabolisms, and particularly their coupling to neuronal functions via lactate, as an essential mechanism for long-term memory formation.